Guidance for approved third parties in Northern Ireland : Payments of Income support, Jobseeker's Allowance (Income Based) and Universal Credit for a child conceived without consent, including rape, or while in a coercive or controlling relationship.: Payments of Income support, Jobseeker's Allowance (Income Based) and Universal Credit for a child conceived without consent, including rape, or while in a coercive or controlling relationship. ([2017]) - Northern Ireland., Department for Communities,
No abstract available